Trait anxiety, sensation seeking, internal-external locus of control in male and female delinquents and non-delinquents - Sherrets, Steve (1973)
Personality research with delinquents has largely produced inconclusive and inconsistent results. Peterson, Quay and Cameron (1959) have pointed out that: Most investigations of personality factors in crime and delinquency have begun with a legally defined sample of offenders, proceeded with comparisons between that group and a more or less carefully matched group of non-offenders, and ended with less ambiguous results